UN NUEVO OCTODONTIDAE (RODENTIA, CAVIOMORPHA) DE LA FORMACIÓN EPECUÉN (PLIOCENO MEDIO) DE HIDALGO (PROVINCIA DE LA PAMPA) (Ameghiniana, 2013)
A new spec.es of the genus Phtoramys, from the Epecuén Formation (Middle Pliocene ), found in La Pampa (Argentina), is described. It is considered that the species of this genus have the type of dental morphology potentially ancestral to the Ctenomyinae Reig, 1958. Through a sequence of known Octodontidae forms an analysis of the probable modification processes which culminated with Ctenomys and similar Pliopleistocene Forms of Argentina is presented; besides the probable causes of such processes are considered. In relation with those processes the validity of "Xenodontomys" simpsoni, J. Kraglievich, 1961, and the relative age of the Río egro Formation ("Rionegrense"). in which it has been found, is d.scussed, The authors consider the Ctenomyinae as being a natural and coherent group.